Bibliography: About Multinational Enterprises, 1970-1973 - Kafka, Folke (1974)
In the last ten years multinational enterprises had experienced a rapid growth, and at the same time, the interest in the subject and its controversies too. This has translated in the appearance of different investigations. This bibliography contains the controversies of the internationalization of production; the transference, commercialization and employment of technologies; in the differences between host country and central country (or parent company); and finally, the controversy of future perspectives. Here we have gathered the research produced in Spanish, Portuguese, English, French and German, between 1970 and 1973.